Connectivity of Targets for Disaster Risk Reduction and Achievement of Sustainable Development Goals - Case Study: Major Flood in DKI Jakarta 2020: (Studi kasus: banjir besar di DKI Jakarta tahun 2020) - Adi Subiyanto (UNIB Press, 2023)
DKI Jakarta is naturally a flood-prone area, thus handling flood in Jakarta is not easy to do so. Success in handling floods will have a positive impact on development activities, as reflected in low economic losses. The purpose of this study is to review the causes and triggers of major flooding in the DKI Jakarta area in 2020 and seek connectivity between targets in the Sendai Framework for Disaster Risk Reduction (SFDRR) and the Sustainable Development Goals (SDGs). Researchers collect library materials from various sources that are used to analyze research problems, followed by drawing conclusions. The results showed that the causes of flooding in DKI Jakarta were geological, geomorphological, and river morphometric factors, while the La Nina phenomenon triggered major floods in 2020. The 2020 floods resulted in an economic loss of IDR 960 billion from DKI Jakarta's gross domestic product (701.98 trillion), so the proportion is 0.137 percent. In other words, success in reducing the risk of flood disasters can reduce economic losses and has indirectly encouraged the achievement of several other targets in the SDGs.